The contribution of some motor skills for the accuracy of the performance of my skills setup and receive transmissions volleyball - Hikmat, Asmaa (Journal of Physical Education, 2011)
Motor abilities are considered one of the important things that affect the level of performance especially setting. Setting is one of the skills that require great abilities that help athletes reach their highest level of achievement. Because these important abilities did not receive much study and research, the researcher aimed at studying setting and receiving by specifying contributes percentage for both skills. The aim of the research: - identifying contribution percentage of some Motor Abilities in performance accuracy of setting and receiving - service in volleyball. The researcher used the descriptive method. The subjects were (30) students. The results showed a contribution percentage on accuracy of performing setting which proves the validity of performance. Finally the results showed effective contribution percentage for accuracy and perception of setting receiving